The “Profiles” document: a modern revision of the objectives of undergraduate medical studies in Switzerland (Swiss Medical Weekly, 2016)
The Joint Commission of the Swiss Medical Schools (SMIFK/CIMS) decided in 2000 to establish a Swiss Catalogue of Learning Objectives (SCLO) for undergraduate medical training, which was adapted from a similar Dutch blueprint. A second version of the SCLO was developed and launched in 2008. The catalogue is a prerequisite for the accreditation of the curricula of the six Swiss medical faculties and defines the contents of the Federal Licensing Examination (FLE). Given the evolution of the field of medicine and of medical education, the SMIFK/CIMS has decided to embark on a total revision of the SCLO. This article presents the proposed structure and content of Profiles, a new document which, in the future, will direct the format of undergraduate studies and of the FLE. Profiles stands for the Principal Relevant Objectives for Integrative Learning and Education in Switzerland. It is currently being developed by a group of experts from the six Swiss faculties as well as representatives of other institutions involved in these developments. The foundations of Profiles are grounded in the evolution of medical practice and of public health and are based on up-to-date teaching concepts, such as EPAs (entrustable professional activities). An introduction will cover the concepts and a tutorial will be displayed. Three main chapters will provide a description of the seven 2015 CanMEDS roles, a list of core EPAs and a series of ≈250 situations embracing the most frequent and current conditions affecting health. As Profiles is still a work in progress, it is hoped that this paper will attract the interest of all individuals involved in the training of medical students.